Pengaruh Good Corporate Governance, Capital Asequasy Ratio, Dan Efisiensi Operasional Terhadap Kinerja Keuangan Bank Umum Syariah Di Indonesia - Agnes Kurnia; Wulan Ramadani Trisnaudy; Yudhistira Ardana; Any Eliza (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2025)
This research investigates how Good Corporate Governance (GCG), the Capital Adequacy Ratio (CAR), and Operational Efficiency (BOPO) influence financial performance measured by Return on Assets (ROA) of Islamic Commercial Banks in Indonesia from 2020 to 2023. Employing a Fixed Effect panel data regression in EViews 12, the study draws upon a purposively sampled set of banks with complete financial disclosures during the period. Prior to estimation, Chow and Hausman tests determined the appropriate model, and diagnostic checks confirmed that residuals met normality, multicollinearity, and heteroscedasticity assumptions. Results reveal that both GCG (p = 0.0315) and CAR (p = 0.0260) positively and significantly affect ROA, whereas BOPO exerts a negative, significant impact (p = 0.0002). An Adjusted R² of 0.3484 suggests that these three variables account for 34.84% of ROA’s variability. Findings align with stakeholder, signaling, and efficiency theories in Islamic banking and corroborate earlier empirical work. Practically, the study underscores the importance of robust governance, adequate capitalization, and cost control to bolster bank profitability. Future research may incorporate macroeconomic indicators or adopt dynamic panel techniques to deepen insights into financial performance drivers.